THE EFFECT OF THE ABILITY TO READ FICTION STORIES ON THE ABILITY TO WRITE FICTION STORY REVIEWS OF GRADE VIII STUDENTS OF MTS AL-HIDAYAH CAGAR ALAM - Hanifatun Salim (STMIK Indonesia Banda Aceh, 2026)
This study aims to determine the effect of the ability to read fictional stories on the ability to write fictional story reviews of class VIII students of MTs Al-Hidayah Cagar Alam. The research is motivated by the low ability of students in understanding the elements of fictional stories and difficulties in compiling systematic and critical reviews . The research method used is a quantitative method with a Pre-Experimental Design in the form of One Group Pretest-Posttest Design. The research sample amounted to 53 students consisting of 28 students of class VIII.1 and 25 students of class VIII.3 . Data collection techniques were carried out through tests of ability to read fictional stories and tests of ability to write fictional story reviews . Data were analyzed using normality tests , homogeneity tests , and hypothesis tests Paired Sample t - Test with the help of SPSS. The results of the study showed an increase in the ability to write fictional story reviews after students received treatment in the form of fictional story reading activities . In class VIII.1 the average value increased from 63.75 to 83.75, while in class VIII.3 it increased from 63.00 to 74.00. The results of the hypothesis test show a significance value (Sig. 2-tailed) of 0.000 < 0.05 so that H₀ is rejected and Hₐ is accepted . Thus , the ability to read fictional stories has a significant influence on the ability to write fictional story reviews of class VIII students at MTs Al-Hidayah Cagar Alam .